Предмет: Математика,
автор: Аноним
Решите уравнение:1,2 х-(6,4-0,4х)=1,3х+(0,4х-5)
Ответы
Автор ответа:
0
1,2х-(6,4-0,4х)=1,3х+(0,4х-5)
1,2х-6,4+0,4х=1,3х+0,4х-5
1,2х+0,4х-1,3х-0,4х=6,4-5
-0,1х=1,4
х=1,4:(-0,1)
х= -14
Ответ: х= -14
1,2х-6,4+0,4х=1,3х+0,4х-5
1,2х+0,4х-1,3х-0,4х=6,4-5
-0,1х=1,4
х=1,4:(-0,1)
х= -14
Ответ: х= -14
Автор ответа:
0
1,2х-(6,4-0,4х)=1,3х+(0,4х-5)
1,2х-6,4+0,4х=1,3х+0,4х-5
1,2х+0,4х-1,3х-0,4х = 6,4-5
-0,1х = 1,4 (: -0,1х)
х = -14
1,2х-6,4+0,4х=1,3х+0,4х-5
1,2х+0,4х-1,3х-0,4х = 6,4-5
-0,1х = 1,4 (: -0,1х)
х = -14
Похожие вопросы
Предмет: Химия,
автор: marinanevgold
Предмет: Английский язык,
автор: kyznecovavaleria223
Предмет: Русский язык,
автор: lera23750
Предмет: Математика,
автор: Vika11234567
Предмет: Математика,
автор: taniamishakova